Alveolar preservation after tooth extraction for later installation of dental implant: a case report (Research, Society and Development, 2022)
There are several causes that can lead to the loss of a dental element, such as: dental fracture, periodontal disease, among others. The removal of this tooth causes the bone tissue that surrounds it to undergo a physiological loss. In order to maintain bone height and thickness (alveolar preservation), for the future rehabilitation of this patient with dental implant, bone graft and membrane are used. Therefore, the objective of this work was to describe the technique performed in a clinical case, in which an alveolus was preserved that, due to its bone deficiency, it was not possible to install an implant. Element 15 was removed due to a root fracture, and the socket was filled with xenogeneic bone graft, along with a resorbable membrane, aiming at preserving this socket for future installation of an implant. It was concluded that alveolar proservation with the use of xenogeneic graft and resorbable membrane is a favorable technique that provided the necessary bone quantity and the preservation of bone walls, enabling a future implant installation.